Labour market outcomes and child marriage: Evidence from BRAC's skills training programme - Rahman, Atiya; Bhattacharjee, Anindita; Rahman, Rehnuma (Bangladesh Institute of Development Studies, 2024)
This article was published in The Bangladesh Development Studies [©2023 Rights managed by BIDS] and the definite version is available at: https://doi.org/10.57138/FFAC8708 The Article's website is at: https://bids.org.bd/page/journal/?rid=1330&vstatus=bds&vissue=current